Gender-Based Poverty Alleviation in Grobogan Regency - Suparno, Suparno (KOMUNITAS: International Journal of Indonesian Society and Culture, 2018)
Indonesia’s human quality is relatively low. Based on the 2017 Human Development Report, the number of the Indonesian Human Development Index (HDI) or Human Development Index (HDI) is 70.81. In detail, the index number is a composite of life expectancy at birth of 70.90 years, Number of Expectations for School Length 12.72 Years, Average School Length 7.95 years, and expenditure per capita Rp. 10,420,000, -. The aim of this paper is analyzing poverty reduction efforts in Grobogan Regency in 2018. Has poverty allieviation been carried out by the Government of Grobogan Regency already taken into account the interests and needs of men and women proportionally? Based on the analysis above, it can be concluded that poverty reduction in Grobogan District has not maximally taken into account the interests of women and men proportionally. In the economic field, women’s ability to access capital has not run smoothly, because some savings and loan businesses managed by women have not run smoothly. In the field of education, women still lag behind men in indicators of long-term school expectations. Likewise the condition of women’s education is still lagging behind that of men, which has an impact on the opportunity to get decent income. Women’s income is lower than that of men. In the field of health and clean water women are still vulnerable to maternal mortality and environmental hygiene.